PTH-014 Food Bolus Obstruction: An Experience from A Large Teaching Hospital. (17th August 2016) - Langoya, CO; O'connor, A; Rembacken, B
Abstract : Introduction: Food bolus obstruction is a common problem encountered by endoscopists with an annual incidence estimated to be around 13 per 100, 000. 1 Several means of endoscopic management have been proposed including extraction, using a snare or a roth net, or pushing, occasionally with dilatation. The aim of this audit was to determine the common types of foodstuffs causing food bolus obstruction (FBO), the prevalence of eosinophilic oesophagitis (EO) among those cases and how different endoscopists in St. James' University Hospital, Leeds handle FBO cases in terms of treatment and subsequent endoscopy follow up. Methods: Two years' data (2014 and 2015) was retrieved from the endoscopy data base in St. James' University Hospital and a total of 33 cases of endoscopy for food bolus obstruction within the specified period were generated and analysed. Excel was used to construct graphs and tables and draw the descriptive statistics (mean, standard deviation, mode and median) of variables. Results: Younger males are found to be more likely affected than females or elderly patients. In 8 cases no food bolus was seen at endoscopy, leaving 25 cases for analysis. In 10 cases (40%) the type of food causing the bolus was not documented. Among the others in 11 cases meat was the cause, 3 times fish and only once vegetables. In 13 cases (52%) the bolus was retrieved with either a snare or Roth net. In 12 cases (48%) it was pushed through, having first been crushed in 5 of these cases. All attempts were successful with no serious adverse events. EO was diagnosed in 24% (n = 6). Reflux was present in 28% (n = 7). One patient had an oesophageal cancer. 4 patients had a pre-existing diagnosis of oesophageal cancer, 1 had a peptic oesophageal stricture and another had a radiation induced stricture. Paired biopsies from upper and lower oesophagus were taken in 68% (n = 17) of cases, of the other 8 five had already been given a histologic diagnosis for their oesophageal stricture (4 malignant, 1 benign) and biopsies were not judged to be needed. Eosinophilic oesophagitis was suspected endoscopically in five cases and confirmed histologically in four of those. In two cases, endoscopic appearances were normal and random paired biopsies identified eosinophilic oesophagitis. Conclusion: FBO is a relatively uncommon presentation even in a large acute unit. The majority of cases are due to benign disease. Endoscopic treatment modalities vary and pushing and removal methods seem to be of equally of good efficacy and safety. Meat bolus is the commonest cause of food bolus obstruction. There is a good diagnostic yield from biopsy. Reference: 1 Longstreth GF, Longstreth KJ, Yao JF. Esophageal food impaction: epidemiology and therapy. A retrospective, observational study. Gastrointest Endosc . 2001 Feb; 53 (2):193–8 Disclosure of Interest: None Declared